Exploring the transversus abdominis plane block in cesarean sections and the subsequent toxicity risk to neonates via breast milk - Joshua Junge; Mario A Inchiosa; Jeff L Xu (Wolters Kluwer Medknow Publications, 2019)
The transversus abdominis plane (TAP) block with its wide application has shown to be an analgesic effective for use in abdominal surgeries, including for cesarean section. However, the bupivacaine delivered in the TAP block comes with the risk of toxicity, both central nerve system (CNS) and cardiovascular system, and has been shown in some instances to reach maximum serum concentrations in excess of the 2 μg/mL associated with the lower end of CNS toxicity. There is a specific concern with cesarean section TAP blocks of the anesthetic passage to the neonate via maternal breast milk and whether this poses a toxicity risk. Bupivacaine has been shown to pass into maternal milk at concentrations 0.34 times the maternal serum concentration. Preliminary statistical analyses suggest that the bupivacaine delivered in breast milk is not in concentrations high enough to cause neonatal toxicity, but further studies would be useful in identifying what the toxicity risk is, if any, to the neonates' breastfeeding after the delivery and TAP block.